Melanoma cutâneo: estudo prospectivo de 42 casos Cutaneous melanoma: a prospective study of 42 cases - Nurimar Conceição Fernandes; Roberto Calmon (Sociedade Brasileira de Dermatologia, 2011)
Estudo longitudinal prospectivo de 42 casos de melanoma cutâneo revelou: 71,2% entre 50 e 79 anos; distribuição etária homogênea entre os gêneros masculino (45,1%) e feminino (54,7%); predominância de brancos (88%); localização no tronco (54,7%) (p=0,039); tipo clínico-histológico expansivo superficial (52,3% / 26,1%) (p=0,02); 16 casos (38,1%) IA e nove melanomas in situ (21,4%). A prospective longitudinal study of 42 cases of cutaneous melanoma showed that: 71.2% of patients were between 50 and 79 years of age; 45.1% were male and 54.7% female; most patients (88%) were white; most lesions (54.7%) were located on the trunk (p = 0.039); the most common clinical and histological pattern was the superficial spreading melanoma (52.3% / 26.1%) (p = 0.02); 16 cases (38.1%) were classified as stage IA and 9 cases (21.4%) consisted of melanomas in situ.